A RISK-BASED CUSTOMS CONTROL SYSTEM IN FREE ZONES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
To support business and promote global trade, the country creates special territories and free zones. Free zones provide entrepreneurs with benefits such as fiscal reliefs, easier access to various resources, and simplified movement of goods, but at the same time create an environment where there are risks of unscrupulous activities. Several studies have concluded that the simplified control of free zone companies and goods implemented by customs authorities poses a high risk of smuggling, violations of intellectual property rights, as well as money laundering. In their research, the authors propose a free zone control model, in which customs risk mitigation measures can be implemented by providing targeted customs control solutions and at the same time without creating additional burdens for entrepreneurs, ensuring fast cargo throughput and increasing the security of international supply chains.